2016
DOI: 10.4314/tjpr.v15i8.13
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of apocynin nitrone in oxygen glucose deprivation-treated SH-SY5Y cells and rats with ischemic stroke

Abstract: Purpose: To investigate the neuroprotective potential of apocynin nitrone (AN-1), a nitrone analogue of apocynin, in rat brain tissue as a novel candidate for ischemic stroke treatment. Methods: In vitro neuroprotection of AN-1 was studied in SH-SY5Y cells treated with oxygen glucose deprivation (OGD). Cell viability was measured using 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay, and intracellular reactive oxygen species (ROS) level was investigated using flow cytometry. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…At the same time, 100 µM AP pretreatment conferred significant protection up to 94% against Fb1-induced cell loss (Figure 6 A(c)). This result is in agreement with a previous report by Liu et al (2016) that demonstrated the neuroprotective effect of AP nitrone in oxygen glucose deprivation-treated SH-SY5Y cells and rats with ischemic stroke. The protective effect of AP was confirmed by morphological observation using a bright-field microscope (Figure 6B).…”
Section: Mtt and Ldhsupporting
confidence: 94%
“…At the same time, 100 µM AP pretreatment conferred significant protection up to 94% against Fb1-induced cell loss (Figure 6 A(c)). This result is in agreement with a previous report by Liu et al (2016) that demonstrated the neuroprotective effect of AP nitrone in oxygen glucose deprivation-treated SH-SY5Y cells and rats with ischemic stroke. The protective effect of AP was confirmed by morphological observation using a bright-field microscope (Figure 6B).…”
Section: Mtt and Ldhsupporting
confidence: 94%
“…Several steps of the ischemic cascade have been targeted by pharmacological treatment strategies to prevent irreversible neuronal damage. Thirty-six studies in undifferentiated SH-SY5Y cell models (Chen et al 2021b ; Dong et al 2021 ; Gao et al 2017 ; Hao et al 2015 ; Hong et al 2017 ; Hsieh et al 2021 ; Huang et al 2021 ; Janssen et al 2021 ; Jiang et al 2012 ; Jimenez-Almarza et al 2019 ; Lai et al 2020 ; Landgraf et al 2020 ; Li et al 2019a , b , 2020a ; Lin-Holderer et al 2016 ; Liu et al 2016 , 2019a , b ; Liu 2016 ; Luan et al 2013 ; Marutani et al 2012 ; Park et al 2017 ; Ruan et al 2021 ; Shi et al 2019 ; Song et al 2019 ; Wang et al 2013 , 2019b , c , 2021a ; Wu et al 2020a , b ; Xu et al 2020b ; Yang et al 2014 ; Zappala et al 2021 ; Zhi et al 2020 ), seven in differentiated SH-SY5Y cell models (Cheng et al 2014 , 2019 ; Fu et al 2020 ; Lin et al 2011 ; Sriwastva et al 2020 ; Zeng et al 2019 ; Zhang et al 2019b ), two in undifferentiated SK-N-SH cell models (Lehane et al 2013 ; Soh et al 2007 ), and one in hiPSC-derived neurons (Pires Monteiro et al 2021 ) included treatment with a pharmacological compound. Treatment targets were neuronal activity, oxidative/nitrosative stress, inflammation, autophagy or cell death.…”
Section: Resultsmentioning
confidence: 99%
“…A growing body of evidence supported that the occurrence of diverse brain diseases is closely related to oxidative stress [36] and the SH-SY5Y cells are recognized as a common model for evaluating the function of nerve cells [37]. In order to explore the neuroprotective activity of diosgenin-amino acids derivatives [38,39,40,41,42], the model of 2,4,5-Trihydroxybutyrophenone (TBHP)-induced neurotoxicity in SH-SY5Y cells has been used as an in vitro research platform in this study. The results were expressed as EC 50 values in Table 2.…”
Section: Resultsmentioning
confidence: 99%